2017
DOI: 10.1186/s12888-017-1233-2
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity is associated with a smaller hippocampus in male but not female depressed in-patients: a case–control study

Abstract: BackgroundThree studies assessed the association of early life adversity (ELA) and hippocampal volumes in depressed patients, of which one was negative and the two others did not control for several potential confounding variables. Since the association of ELA and hippocampal volumes differ in male and female healthy volunteers, we investigated the association of ELA and hippocampal volumes in depressed patients, while focusing specifically on sex and controlling for several relevant socio-demographic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…These volume changes suggest that hippocampal volume may one day be a useful biomarker of depression and/or antidepressant efficacy, though high intrinsic variability currently precludes this. In addition, although the aforementioned effects were observed in mixed sex subject groups, and differences have been observed in at least one study using only female subjects (Tae et al, 2011), several reports suggest that decreased hippocampal volume due to stress and depression is more apparent in males than in females (Carlson et al, 2017; Colle et al, 2017; Frodl et al, 2002; Spalletta et al, 2014). The association of low hippocampal volume with depression suggests that stress and hippocampal changes may be important drivers of depression (Lupien et al, 2007; Maller et al, 2017).…”
Section: Stress and Depression Decrease Hippocampal Volumementioning
confidence: 96%
“…These volume changes suggest that hippocampal volume may one day be a useful biomarker of depression and/or antidepressant efficacy, though high intrinsic variability currently precludes this. In addition, although the aforementioned effects were observed in mixed sex subject groups, and differences have been observed in at least one study using only female subjects (Tae et al, 2011), several reports suggest that decreased hippocampal volume due to stress and depression is more apparent in males than in females (Carlson et al, 2017; Colle et al, 2017; Frodl et al, 2002; Spalletta et al, 2014). The association of low hippocampal volume with depression suggests that stress and hippocampal changes may be important drivers of depression (Lupien et al, 2007; Maller et al, 2017).…”
Section: Stress and Depression Decrease Hippocampal Volumementioning
confidence: 96%
“…Further bolstering connections between ELS and illness progression, a meta-analysis found that a history of childhood maltreatment was associated with a greater probability of developing recurrent and persistent cycles of depression as well as treatment-resistance (56). Imaging studies have also demonstrated that an ELS history was associated with hippocampal and mPFC volumetric decline (57)(58)(59)(60)(61)(62)(63)(64)(65). Some of these studies have noted that the relationship may be independent of the presence of MDD (61,64,65).…”
Section: Stress and Hippocampal/mpfc Volume Reduction In Mddmentioning
confidence: 99%
“…Recent studies show no sex differences in hippocampal volume across development [32]. One caveat in these studies is that a number of factors that influence hippocampal volume are not often documented including early adversity (reductions are often seen in men but not in women: [33]), phase of menstrual cycle [34], parity status [35], hormone therapy [36], menopausal status [37], genotype [38], and testosterone levels in men [39]. Researchers are cautioned that these variables need to be considered to obtain an accurate understanding of sex differences in the volume of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%